Immunomodulatory Role of Nutrients: How Can Pulmonary Dysfunctions Improve? - Gozzi-Silva, Sarah Cristina; Teixeira, Franciane Mouradian Emidio; Duarte, Alberto José da Silva; Sato, Maria Notomi; Oliveira, Luana de Mendonça (Frontiers in Nutrition, 2021)
Nutrition is an important tool that can be used to modulate the immune response during infectious diseases. In addition, through diet, important substrates are acquired for the biosynthesis of regulatory molecules in the immune response, influencing the progression and treatment of chronic lung diseases, such as asthma and chronic obstructive pulmonary disease (COPD). In this way, nutrition can promote lung health status. A range of nutrients, such as vitamins (A, C, D and E), minerals (zinc, selenium, iron, and magnesium), flavonoids and fatty acids, play important roles in reducing the risk of pulmonary chronic diseases and viral infections. Through their antioxidant and anti-inflammatory effects, nutrients are associated with better lung function and a lower risk of complications since they can decrease the harmful effects from the immune system during the inflammatory response. In addition, bioactive compounds can even contribute to epigenetic changes, including histone deacetylase (HDAC) modifications that inhibit the transcription of proinflammatory cytokines, which can contribute to the maintenance of homeostasis in the context of infections and chronic inflammatory diseases. These nutrients also play an important role in activating immune responses against pathogens, which can help the immune system during infections. Here, we provide an updated overview of the roles played by dietary factors and how they can affect respiratory health. Therefore, we will show the anti-inflammatory role of flavonoids, fatty acids, vitamins and microbiota, important for the control of chronic inflammatory diseases and allergies, in addition to the antiviral role of vitamins, flavonoids and minerals during pulmonary viral infections, addressing the mechanisms involved in each function. These mechanisms are interesting in the discussion of perspectives associated with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and its pulmonary complications since patients with severe disease have vitamins deficiency, especially vitamin D. In addition, researches with the use of flavonoids have been shown to decrease viral replication in vitro. This way, a full understanding of dietary influences can improve the lung health of patients.